1992
DOI: 10.1111/j.1464-410x.1992.tb15862.x
|View full text |Cite
|
Sign up to set email alerts
|

Terazosin in the Treatment of Benign Prostatic Hyperplasia: A Multicentre, Placebo‐Controlled Trial

Abstract: The dynamic component of bladder outflow obstruction due to benign prostatic hyperplasia (BPH) has been shown to be modified by alpha 1 adrenergic receptors. Terazosin is an alpha 1 receptor-blocking agent with a long half-life permitting once-daily dosing. This drug was administered in a multicentre, randomised, placebo-controlled trial involving patients with symptomatic bladder outflow obstruction. Of 132 patients recruited for the study, 86 were randomised to receive placebo or terazosin, 81 completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 8 publications
0
22
0
2
Order By: Relevance
“…Previous studies have demonstrated the efficacy of ter azosin as a treatment for the symptoms of BPH [3][4][5][6][7][8][9][10]. In the first part of this study, nearly half of the patients bene fited sufficiently to justify long-term treatment.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies have demonstrated the efficacy of ter azosin as a treatment for the symptoms of BPH [3][4][5][6][7][8][9][10]. In the first part of this study, nearly half of the patients bene fited sufficiently to justify long-term treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Terazosin is a long-acting apselective blocking agent that was originally used for the treatment of arterial hypertension. The effects of terazosin on symptom scores and urinary flow rates have been previously documented [3][4][5][6][7][8][9][10], This randomized, placebo-controlled, double-blind, multicentre study was performed to evaluate the long term efficacy and safety of terazosin in the treatment of patients with BPH. While many terazosin studies have focused primarily on changes in symptom scores and flow rates, this study examines four additional aspects of terazosin therapy: (1) changes in patient quality-of-life (QOL); (2) the effect of randomized withdrawal following an initial treatment period; (3) the effect of terazosin on prostate-specific antigen (PSA) in a prospective study, and (4) the effect of terazosin on blood pressure in normotensive and hypertensive patients, whether or not the patients were controlled with other antihypertensive ther apy.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49] Significant improvement in symptoms has been reported with alfuzosin treatment.33-37'50-52 A significant increase in Qmax has been reported in one study37 but not others. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Tamsulosin exhibits relative selectivity for the a)A-adrenoceptor subtype and is associated with symptom and Qmax improvements similar to those obtained with terazosin, doxazosin, and alfuzosin.53-55 This agent can be administered under a oncedaily dosage schedule with reduced need for dose titration.…”
Section: Microwave Treatmentmentioning
confidence: 96%
“…Buna karşın diSilverio'nun 137 vakalık serisinde semptom skoru ve idrar akım çalışmalarında terazosinin plasebodan daha iyi etkisi olsa da elde edilen sonuçların istatistiksel öneme ulaşmadığı bildirilmiştir (20). Lloyd ise 86 olguda 8 haftalık terazosin (2-5-10 mg/gün) kullanımıyla plasebo düzeyinde bile maksimum idrar akım hızı sağlayamadığını ve semptomatik düzel-menin de önceki seriler kadar önemli olmadığını bildirmiştir (21). Ancak Llyod'un bu çalışmasında plaseboyla elde ettiği maksimum idrar akım hızı artışının çok yüksek olması dikkat çekicidir.…”
Section: T Ta Ar Rt Tı ış şM Ma Aunclassified